Building Resilient Elementary Schools in the Digital Era: Integrating Deep Learning Pedagogy and Artificial Intelligence - Hariyadi, Slamet; Subaharianto, Andang; Siswati, Bea Hana; Shah, Dianna Suzieanna Mohamad (Universitas Lambung Mangkurat, 2025)
Small elementary schools often face serious challenges, particularly in terms of low student enrollment, limited community support, and insufficient teacher capacity to meet curriculum and technological demands. SDN Temenggungan in Banyuwangi is one such school that, at one point, did not receive any new student enrollments. Through a community service program based on a participatory action approach, teachers were supported in designing and implementing student-centered, inquiry-oriented learning strategies (“deep learning” in a pedagogical sense) and introduced to artificial intelligence (AI) as a learning tool through simple digital tools and chat-based applications. The program resulted in a significant increase in new student enrollment, improved teacher competence in lesson design and technology integration, and a positive shift in community perception toward the school. The participatory approach proved effective in fostering teacher engagement and ownership of instructional innovations. These quantitative outcomes substantiate the program’s impact on both pedagogical quality and community trust. Such an initiative can serve as a replicable model for empowering teachers in other elementary schools facing similar challenges in different regions.